2019
DOI: 10.1186/s12884-019-2649-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dietary practice and nutritional status of pregnant women in Dessie town, northeastern Ethiopia: a community-based cross-sectional study

Abstract: BackgroundMaternal undernutrition is highly prevalent in resource-poor settings. Hence, this study was intended to determine factors associated with the dietary practice and nutritional status of pregnant women in Dessie town, northeastern Ethiopia.MethodsCommunity-based cross-sectional study design was employed. Six hundred four (604) pregnant women have participated. A two-stage sampling method was applied to select participants. Socio-demographic and socio-economic data were collected using a structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
67
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 16 publications
20
67
5
3
Order By: Relevance
“…The current study found 21.8% (MUAC<23) prevalence rate of undernutrition. Our result is consistent with those of other three studies carried out in other parts of Ethiopia 19.8%, 19.5% and 24% (23,31,32). It is also consistent with ndings of a study done in south Sudan and a systemic review in Africa reported 18.9% and 23.5% respectively (20,33) .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The current study found 21.8% (MUAC<23) prevalence rate of undernutrition. Our result is consistent with those of other three studies carried out in other parts of Ethiopia 19.8%, 19.5% and 24% (23,31,32). It is also consistent with ndings of a study done in south Sudan and a systemic review in Africa reported 18.9% and 23.5% respectively (20,33) .…”
Section: Discussionsupporting
confidence: 93%
“…The odds of undernutrition among women with poor nutritional knowledge were higher than their counterparts. This nding is similar with previous study (23). This could be possibly due to that poor nutritional knowledge about basic nutrition usually results in poor dietary intake leading to undernutrition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These articles were from six regional state and two cities of Ethiopia. Eight studies were done in Oromo regional state [25,26,28,30,31,33,46,47], six articles in Amhara region [32,[48][49][50][51][52], four articles from South Nation and Nationality of People (SNNP) [27,34,53,54], two articles in Tigray [29,55] and in Addis Ababa (AA) [56], Dire Dawa [57], Gambella [58] and Ethiopian Somalia [59] shared single articles for each.…”
Section: Explanation For Original Studiesmentioning
confidence: 99%